Investigation of fluorapatite crystallization in a fluidized bed reactor for the removal of fluoride from groundwater. Issue 2 (10th September 2018) - Deng, Linyu; Zhang, Xiao; Huang, Tinglin; Zhou, Jianqi
Abstract: BACKGROUND: This work further investigates fluoride removal from groundwater by induced crystallization in batch experiments and in a fluidized bed reactor (FBR). Phosphate rock (PR), which is an abundant ore and represents the basic raw material for the phosphatic fertilizer industry, was used as seed crystal in the induced crystallization process. RESULTS: Induced crystallization in FBR reduced the concentration of F − in synthetic groundwater from 9.5 mg L ‐1 to <1.0 mg L ‐1 . Phases with the potential for precipitation were calculated through thermodynamic equilibrium modeling. The formed precipitates were identified by powder x‐ray diffraction (XRD) and scanning electron microscopy, coupled with energy dispersive spectroscopy (SEM–EDS). Finally, fluorapatite crystallization mechanisms were confirmed by the induced crystallization of Ca5 (PO4 )3 F on the surface of PR. CONCLUSION: The fluorapatite crystallization process in FBR removed F − from groundwater, and the used seed crystal PR was rich in phosphorus and that could be recovered as raw material for the phosphatic fertilizer industry. © 2018 Society of Chemical Industry